Quercetin and doxorubicin co-delivery using mesoporous silica nanoparticles enhance the efficacy of gastric carcinoma chemotherapy - Fang, Jian (Int J Nanomedicine, 2018)
BACKGROUND: Effective gastric carcinoma (GC) chemotherapy is subject to many in vitro and in vivo barriers, such as tumor microenvironment and multidrug resistance. MATERIALS AND METHODS: Herein, we developed a hyaluronic acid (HA)-modified silica nanoparticle (HA-SiLN/QD) co-delivering quercetin and doxorubicin (DOX) to enhance the efficacy of GC therapy (HA-SiLN/QD). The HA modification was done to recognize overexpressed CD44 receptors on GC cells and mediate selective tumor targeting. In parallel, quercetin delivery decreased the expression of Wnt16 and P-glycoprotein, thus remodeling the tumor microenvironment and reversed multidrug resistance to facilitate DOX activity. RESULTS: Experimental results demonstrated that HA-SiLN/QD was nanoscaled particles with preferable stability and sustained release property. In vitro cell experiments on SGC7901/ADR cells showed selective uptake and increased DOX retention as compared to the DOX mono-delivery system (HA-SiLN/D). CONCLUSION: In vivo anticancer assays on the SGC7901/ADR tumor-bearing mice model also revealed significantly enhanced efficacy of HA-SiLN/QD than mono-delivery systems (HA-SiLN/Q and HA-SiLN/D).